The impact of methylprednisolone and rituximab on podocyte injury caused by puromycin aminonucleoside - Wang, Li; Zhao, Manman; Zhu, Jialiang; Hua, Ran; Zhu, Ying; Deng, Fang (Frontiers in Cell and Developmental Biology, 2025)
IntroductionTo explore how MP and RTX impact TRPC6's expression and localization, and assess MP's and RTX's effects on podocyte injury and recovery.MethodsMPC5 cells were simultaneously grown alongside a control group and under various conditions: exposure to puromycin aminonucleoside (PAN) stimulation, treatment with methylprednisolone (MP), and treatment with rituximab (RTX), and a combined treatment with both MP and RTX.ResultsAt 8, 24, and 48 h, CCK-8 assay showed that PAN (50 μg/mL) had a decrease in cell viability and an increase in cell death, and it could be used as the optimum concentration to induce podocyte injury; MP (100 ng/mL) and RTX (100 μg/mL) maintained cell viability and had minimal impact on cell morphology, and they were the best concentrations. Following 24 and 48-h exposure to MP or RTX, there was a decrease of 30%–50% in apoptosis rates by flow cytometry in comparison to the group stimulated with PAN, accompanied by a substantial reduction in nearly 10%–60% of TRPC6 mRNA and 5%–20% of protein levels which were measured using qRT-PCR and western blot analyses, akin to the observed decrease in levels of IL-1β and IL-18. Additionally, calcium entry showed considerable reductions after 8, 24, and 48 h of MP treatment relative to the PAN-stimulation group, paralleling the effect seen with 24-h RTX treatment.DiscussionTherefore, MP and RTX safeguarded podocytes, and averted proteinuria by decreasing podocyte apoptosis, diminishing TRPC6 mRNA and protein levels, and suppressing inflammatory markers and calcium entry.